Pengaruh Senam Hamil terhadap Penurunan Nyeri Punggung Bawah pada Ibu Hamil Trimester II dan III Di BPM Maya Kabupaten Batubara - Agustina Elsera Tarigan; Adelina Sembiring; Lisbet Gurning (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
During the second and third trimesters of pregnancy, as fetal development progresses, pregnant women often experience lower back pain. This condition not only causes discomfort but also affects daily activities and overall quality of life. One of the non-pharmacological approaches believed to reduce lower back pain is prenatal exercise. This study aims to evaluate the effect of pregnancy exercise on reducing lower back pain among pregnant women in the second and third trimesters. This research employed a quasi-experimental design with a pre-post test approach without a control group. The sample consisted of 28 pregnant women in their second and third trimesters who met the inclusion criteria and reported experiencing lower back pain. Pain levels were assessed before and after the intervention using a valid and reliable pain scale. Data were analyzed using appropriate statistical tests, particularly the paired sample t-test. The findings revealed that the mean pain score before the intervention was 3.32 with a standard deviation of 0.772. After the intervention, the mean pain score decreased to 2.25 with a standard deviation of 1.005. Results of the paired t-test indicated a p-value of 0.000 (p < 0.05), demonstrating a significant difference in pain levels before and after pregnancy exercise. These results indicate that pregnancy exercise is effective in reducing lower back pain in women during the second and third trimesters of pregnancy. Therefore, prenatal exercise can be recommended as a safe, simple, and beneficial non-pharmacological intervention in midwifery care. It is expected that this study provides scientific evidence supporting the role of pregnancy exercise in improving maternal comfort and quality of life throughout pregnancy.